Hardware Trojan attacks on voltage scaling‐based side‐channel attack countermeasure. Issue 3 (19th March 2019) - Yu, Weize
Abstract : Here, the side‐channel attack (SCA)‐resistant cryptographic chip: a cryptographic circuit employs a voltage scaling technique is studied with hardware Trojan attacks. Two different types of hardware Trojans, sequential hardware Trojan and combinational hardware Trojan, are proposed to be embedded into the SCA‐resistant cryptographic chip for leaking the secret key. Moreover, the sequential Trojan can only disclose a single bit of the secret key at a time, while the combinational Trojan is able to leak the whole bit of the secret key at once. As demonstrated in the results, only analysing ∼270 (150) power traces are sufficient to disclose the 8‐bit secret key of the sequential (combinational) Trojan‐infected chip to the adversary. Furthermore, both the sequential and combinational Trojan‐infected chips can evade the testing of the power attack and be detected with the proposed statistical models successfully.